(untitled) (Stamford Journal of Pharmaceutical Sciences, 2011)
Key words: Ficus Hispida Linn.; DPPH free radical scavenging; antioxidant; cytotoxicity DOI: http://dx.doi.org/10.3329/sjps.v3i2.8035 S.J. Pharm. Sci 3(2): 29-36